Predicting and visualizing cost propagation due to engineering design changes - Georgiades, Alexandros; Sharma, Sanjiv; Kipouros, Timoleon; Savill, Mark (Design Society, 2017)
During product development changes in the initial design are ubiquitous. The ability to predict such changes, along with the expected costs, is a challenge on its own. This challenge increases exponentially when a single design change on one element of the system propagates to other components. As change propagates, so does the cost associated with it; where cost is more than just financial. A number of knowledge-based methods have been developed in the past that assist in the prediction of how change propagates through a system, and the impact that it can have on other components. None of the methods developed, however, considers how cost propagates due to design changes. This paper presents a novel methodology for predicting, visualizing, and assessing the propagation of change and the cost associated with it. As part of the methodology, a new method, CP2, has been developed to calculate the propagated costs. The methodology has been applied to a conceptual example of a simple system to demonstrate the procedure and the use of the methods. The visualization of the results arising from this methodology is also demonstrated as a mechanism for design decision-making.
Keywords: Design methodology; Design methods; Design costing; Visualisation; Decision making